2003
DOI: 10.1046/j.1475-097x.2003.00498.x
|View full text |Cite
|
Sign up to set email alerts
|

A prolonged postinspiratory pause enhances CO2 elimination by reducing airway dead space

Abstract: SummaryBackground: CO 2 elimination per breath (V CO 2 , T ) depends primarily on tidal volume (V T ). The time course of flow during inspiration influences distribution and diffusive mixing of V T and is therefore a secondary factor determining gas exchange. To study the effect of a postinspiratory pause we defined Ômean distribution timeÕ (MDT) as the mean time given to inspired gas for distribution and diffusive mixing within the lungs. The objective was to quantify changes in airway dead space (V Daw ), sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 29 publications
2
23
3
Order By: Relevance
“…Our results agree with previous findings that a postinspiratory pause enhances CO 2 elimination in healthy or surfactantdepleted animals (4,10,11,20) and with those obtained in surfactant-depleted pigs in which inspiration at pressure-controlled ventilation was prolonged (13). They also agree with results in patients with ALI/ARDS (2,8,12,14).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results agree with previous findings that a postinspiratory pause enhances CO 2 elimination in healthy or surfactantdepleted animals (4,10,11,20) and with those obtained in surfactant-depleted pigs in which inspiration at pressure-controlled ventilation was prolonged (13). They also agree with results in patients with ALI/ARDS (2,8,12,14).…”
Section: Discussionsupporting
confidence: 92%
“…In humans, equilibration through collateral channels may play a role in this. However, Uttman and Jonson made similar observations in healthy pigs, which do not have collaterals (20).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In accordance with the hypothesis based upon previous studies, ΔV E CO 2 increased in relation to lnMDT [16,17]. A better fit of a logarithmic equation rather than a linear one agrees with concepts based upon physiology and morphology.…”
Section: Partsupporting
confidence: 77%
“…Uttman et al showed in healthy pigs that CO 2 elimination depends on time available for gas distribution and diffusion within the respiratory zone, mean distribution time (MDT) [16]. Variation of MDT was achieved by changing the duration of the postinspiratory pause (T P ).…”
Section: Introductionmentioning
confidence: 99%